Islamic Corporate Governance dalam Memoderasi Hubungan antara Kinerja Keuangan dan Islamic Social Reporting - Maya Mahardikasari; Y. Anni Aryani (ITB AAS INDONESIA Surakarta, 2019)
This purpose of this study is to present empirical evidence the effect of islamic corporate governance in moderating the relationship between financial performance and islamic social reporting on islamic banks in Indonesia. As a moderating variabel, the proxie of islamic corporate governance is the score of sharia supervisory board. The population in this study is islamic banks registered in Otoritas Jasa Keuangan (OJK) during the period 2008-2017. The total of population is 13 companies which are the number of samples from the study. This study uses a data panel model that was analyzed using software Eviews 10. Analysis result prove that financial performance affects on islamic social reporting while islamic corporate governance cannot moderate the relationship between financial performance and islamic social reporting. For the control variables, company size has an effect on islamic social reporting but leverage has no effect on islamic social reporting.